The Antibacterial Effect of Ethanol Extract of Garlic (Allium sativum L.) on Methicillin Resistant Staphylococcus aureus (MRSA) In Vitro - Utami Meilanie Putri; Maftuchah Rochmanti; Manik Retno Wahyunitisari; Rebekah J. Setiabudi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: To determine the antibacterial activity of ethanol extract of garlic against Methicillin-ResistantStaphylococcus aureus. Method: Dilution test was performed on 9 different concentration of ethanol extractof garlic (1024, 512, 256, 128, 64, 32, 16, 8, 4 mg/mL) dissolved in DMSO 10% and MRSA suspensionon Mueller Hinton broth medium to determine the Minimum Inhibitory Concentration. The MinimumBactericidal Concentration was determined by the result of streaking of MRSA inoculation on the nutrientagar plate. Results: The observation through Mueller Hinton broth medium has shown turbidity both beforeand after incubation because of garlic ethanol extract color which is blackish-brown and thick, while in thenutrient agar medium, MRSA bacteria grew on the media with concentrations 4, 8, 16, 32, 64, & 128 mg/mL and unable to grow at concentrations of 256, 512, and 1024 mg/mL. Conclusion: The MIC of ethanolextract of garlic on MRSA could not be determined, and the MBC in this study was 256 mg/mL.